Key strategies for maximizing the effectiveness of virtual teams in the Malaysian construction industry - A. A., Manea; A. R., Radzi; R. A., Rahman; A. T., Haron (Universiti Malaysia Pahang, 2020)
Technology has contributed to the development of the construction sector. Scientific discoveries have resulted in the cooperation of a group of people from different geographic locations who depend on communication technologies (i.e., a virtual team). Virtual teams use advanced technology to fix communication issues and are considered as a practical, productive, and creative team concept. Thus, it is evident that the virtual team also needs to concern about improving construction efficiency. This study aims to define the strategies that maximize the effectiveness of virtual teams in the construction industry in Malaysia. To achieve the objective, a questionnaire survey was conducted with industry practitioners from the Malaysian construction industry. The results reveal that seven strategies are perceived by industry practitioners to be both the most effective and easiest in enhancing virtual teams. Conversely, ten strategies are either most effective or easiest to be implemented. This research adds to the body of knowledge is in expanding the understanding of virtual teams in the construction industry in Malaysia, which could support industry practitioners in the decision-making process for improving virtual teams. The findings of this research would help increase the efficiency of the project teams in the construction industry.